Cytokine and cellular responses to human herpesvirus‐6B in patients with B‐acute lymphoblastic leukemia. (6th December 2016) - Nefzi, Faten; Lambert, Claude; Gautheret‐Dejean, Agnès; Fisson, Sylvain; Khebizi, Quentin; Khelif, Abderrahim; Agut, Henri; Aouni, Mahjoub
ABSTRACT: Primary infection with human herpesvirus‐6 (HHV‐6), is followed by its lifelong persistence in the host. Most T‐cell responses to HHV‐6 have been characterized using peripheral blood from healthy adults; however, the role of HHV‐6 infection in immune modulation has not been elucidated for some diseases. Therefore, in this study the immune response to HHV‐6 infection in patients with B‐acute lymphoblastic leukemia (B‐ALL) was analyzed. HHV‐6 load was quantified in blood samples taken at the time of diagnosis of leukemia and on remission. The same concentrations of anti‐ and pro‐inflammatory cytokines (IL‐4, IL‐1, IL‐6, IL‐8, IL‐12p70, IL‐17a, TNF‐α and IFN‐γ) were detected in plasma samples from 20 patients with and 20 without detectable HHV‐6 virus loads in blood. Characterization of T‐cell responses to HHV‐6 showed low specific T‐cells frequencies of 2.08% and 1.46% in patients with and without detectable viral loads, respectively. IFN‐γ‐producing T cells were detected in 0.03%–0.23% and in 0%–0.2% of CD4+T cells, respectively. Strong production of IL‐6 was detected in medium supernatants of challenged T‐cells whatever the HHV‐6 status of the patients (973.51 ± 210.06 versus 825.70 ± 210.81 pg/mL). However, concentrations of TNF‐α and IFN‐γ were low. Thus, no association between plasma concentrations of cytokines and detection of HHV‐6 in blood was identified, suggesting that HHV‐6 is not strongly associated with development of B‐ALL. The low viral loads detected may correspond with latently infected cells. Alternatively, HHV‐6B specific immune responses may be below the detection threshold of the assays used.